Endodontic therapy of maxillary second molar showing an unusual internal anatomy - Carlos Eduardo Fontana; Carolina Davoli Macedo Ibanéz; Felipe Davini; Alexandre Sigrist De Martin; Cláudia Fernandes de Magalhães Silveira; Daniel Guimarães Pedro Rocha; Carlos Eduardo da Silveira Bueno (Revista Sul-Brasileira de Odontologia, 2013)
The knowledge of the complex anatomy of maxillary molars and location of extra canals are essential for diagnosis and endodontic treatment success. Objective: The purpose of this study was to report a clinical case showing a varying number of palatal roots in a second maxillary molar with the aid of operating microscope (OM). Case report: A four-rooted maxillary permanent second molar with 2 separated palatal canals undergone endodontic therapy. After endodontic access, examination of the chamber floor using an operating microscope revealed two distinct palatal canals orifices. A radiograph was taken after the working lengths of each canal were estimated by means of an electronic apex locator which clearly identified the four roots with independent four canals. The canals were instrumented with ProTaper™ rotatory instruments under irrigation with 5% sodium hypochlorite, obturated with Pulp Canal Sealer® and continue wave technique. After completion of root canal treatment, the tooth was restored with composite resin. Results: After endodontic access, the presence of two different palatal canals was found in a second maxillary molar, resulting from a variation in the number of palatal roots of this tooth. Conclusion: The high magnification and clear illumination quality provided by the dental operating microscope increase endodontic treatment success of the variations in the internal anatomy of the tooth.